(untitled) (Malaysian Journal of Civil Engineering, 2018)
Introducing fibres into concrete not only enhances the requisite properties of reinforced concrete but also changes the material characteristic from brittle to ductile failure. Steel fibre (SF) is found to enhance the flexural and tensile strengths, and at the same time is able to resist the formation of macro cracking and concrete spalling. Meanwhile, polypropylene fibre (PPF) will contribute to the tensile strain capacity and compressive strength, and also delaying the formation of micro cracks. Therefore, the mechanical properties of concrete are discussed in this paper of which SF and PPF are combined and mixed together in concrete. For this purpose, hooked-end type deformed steel fibre and fibrillated type virgin polypropylene fibre are used in the experimental work where the concrete strength is maintained for grade C30. The specimens incorporated with SF and PPF are different in terms of its percentage proportions, however, the total volume fraction is fixed at 1.5%. The experimental result shows that the percentage proportion containing 75% SF and 25% PPF produced the highest flexural and tensile strengths with an increase of 45.89% and 25.93%, respectively than that of the plain concrete. For flexural toughness, specimen with 100% SF and 0% PPF produced the highest value of 66.6 Joule. Meanwhile, for compressive strength, there is not much contribution for both SF and PPF to the mechanical properties of the concrete.